2004
DOI: 10.1530/eje.0.1510087
|View full text |Cite
|
Sign up to set email alerts
|

Intrafollicular expression of matrix metalloproteinases and their inhibitors in normally ovulating women compared with patients undergoing in vitro fertilization treatment

Abstract: Objective: To assess possible differences in the activity of matrix metalloproteinases (MMPs), MMP-2 and MMP-9, and their inhibitors, the tissue inhibitors of MMPs, TIMP-1 and TIMP-2, in follicular fluid (FF) of women undergoing in vitro fertilization (IVF) treatment and of normally ovulating women. Design: Prospective study. Methods: MMP-2 and MMP-9 activity was analyzed by gelatin zymography and MMP-2, MMP-9, TIMP-2, TIMP-1 and 17b-estradiol levels were measured in FF by ELISA. Results: We found significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…This finding is consistent with the results of previous animal studies, showing that TIMP-2 mRNA expression was not changed during ovulation in the rat , mouse (Inderdeo et al, 1996) or cow (Smith et al, 1995). Moreover, a comparative study of follicular fluids from IVF cycles and normal menstrual cycles showed no difference in TIMP-2 protein levels between the two groups (D'Ascenzo et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with the results of previous animal studies, showing that TIMP-2 mRNA expression was not changed during ovulation in the rat , mouse (Inderdeo et al, 1996) or cow (Smith et al, 1995). Moreover, a comparative study of follicular fluids from IVF cycles and normal menstrual cycles showed no difference in TIMP-2 protein levels between the two groups (D'Ascenzo et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…This is now recognized as being due to the activity of MMP-2 and MMP-9. A recent study found that the concentration of MMP-2 and MMP-9 protein in human follicular fluid of natural and IVF cycles was similar during the pre-ovulatory stage of natural cycle and IVF cycles (D'Ascenzo et al, 2004). On the contrary, studies in the rat have demonstrated that the highest expressions of these tissue-remodelling enzymes were in the theca and the surrounding stroma (Reich et al, 1991;Curry et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdallah et al [25] reported similar follicular fluid levels of MMPs in patients following a clomiphene citrate cycle and patients undergoing IVF treatment with recombinant stimulating hormone. D'ascenzo et al [26] found lower levels of MMP-2 and MMP-9 in the follicular fluid of IVF patients compared to women with normal ovulation, and suggested that gelatinase levels are influenced by the steroidogenesis induced by the gonadotropin protocol for IVF treatment. This study was the first to compare the follicular fluid levels of MMPs using different drug protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we sought to investigate the possible link between MMPs and the down-regulation of N-cadherin in human OSE. To do so, we first examined the expression of MMP-2 and MMP-9, which have been identified in follicular fluid during follicle growth and ovulation (33,34) in OSE. As shown in Fig.…”
Section: Inhibitor Of Matrix Metalloproteinase Inhibits the Camp-medimentioning
confidence: 99%